Pentingnya Endhorphin Massage terhadap Nyeri Punggung Ibu Hamil Trimeser III - Nirwana Marsanda; Nurilawati Dg. Maroa; Desy Hardiana; Indira indriani; Putri Lutviah Ridwan (Journal on Education, 2023)
The purpose of this study was to determine the effect of Endorphin Massage on back pain in third trimester pregnant women. In the third trimester of pregnancy, as the uterus grows and weight increases, the center of gravity will move forward so that pregnant women have to adjust their standing position. Improper posture will force additional stretching and fatigue on the body. The pressure of the baby's head against the lower back causes back pain in pregnant women. Low back pain is discomfort that occurs below the ribs and above the inferior glueteal. Warm compresses and endorphin massage are non-pharmacological therapies that are useful for reducing back pain experienced by third trimester pregnant women. This type of research is qualitative. Sources of data collected through interviews, observation (observation), questionnaires, and documentation. The body produces endorphins which have different benefits and uses. The various benefits and uses of endorphins which you get from endorphin massage are: Can control pain that persists in the body, Controls addiction to chocolate, Controls emotions, frustration, stress experienced by pregnant women, Makes you more relaxed, so you can reduce feelings of inadequacy comfortable during labour. Regulates the production of growth and sex hormones, Reduces symptoms that interfere with appetite, Boosts the immune system, Slows down the aging process, Endorphin hormones are natural hormones and are produced by the human body, so endorphins are the safest and best pain relievers for the body .